High intensity exercise assessment: relationships between laboratory and field measures of performance - Baker, J. S.; Davies, B. (Journal of Science and Medicine in Sport, 2002)
The purpose of this study was to examine the relationship between high intensity cycle ergometry when resistive forces were optimised and field tests of high intensity performance in an elite sprint trained group (n = 12). Body mass, stature and age of the group were determined prior to testing (66.3 +/- 9.8kg, 177 +/- 7.6cm and 17 +/- 0.74 yrs respectively). Field tests of high intensity performance examined included sprinting. maximal shuttle running and jumping ability (vertical and horizontal). Significant correlations existed between all field tests (P < 0.01). Only moderate correlations were observed for values generated on the cycle ergometer and performance tests (P > 0.05). The results of the present study suggest that the optimised cycle ergometer test and the performance tests are unrelated when evaluated statistically. These findings also suggest that the sprinting and jumping tests examined are highly related and may be substituted for each other as possible predictors of high intensity ability.